4D Printed Stimuli-Responsive Polypills for Personalized Drug Therapy: Advances, Challenges, and Future Perspectives - Zanooja*, Abdul Manaf Fathima (Journal of Pharmacy Practice and Community Medicine, 2026)
Four-Dimensional (4D) printing is transforming pharmaceutical manufacturing by enabling the development of adaptive drug delivery systems capable of responding dynamically to physiological and environmental stimuli. Among the most promising innovations in this field are 4D printed stimuli-responsive polypills, which integrate multiple active pharmaceutical ingredients within a single programmable dosage form capable of controlled and personalized drug release. These systems utilize smart biomaterials including hydrogels, shape-memory polymers, and stimuli-responsive composites that react to triggers such as pH, temperature, enzymes, moisture, magnetic fields, and light. This review explores recent advancements in 4D pharmaceutical printing technologies, adaptive release mechanisms, biomaterials engineering, nanotechnology integration, and artificial intelligence-assisted drug delivery systems. Furthermore, the review discusses the potential applications of adaptive polypills in chronic disease management, including cardiovascular diseases, diabetes, cancer, neurological disorders, and inflammatory diseases. Major challenges involving manufacturing complexity, scalability, regulatory approval, material biocompatibility, long-term safety, and ethical considerations are also critically analyzed. Emerging developments in biosensor integration, wearable health technologies, and AI-driven precision therapeutics indicate that 4D printed polypills may significantly reshape future personalized medicine. Despite current limitations, ongoing interdisciplinary advancements suggest strong future clinical potential for intelligent adaptive pharmaceutical systems.
Keywords: 4D Printing; Adaptive Drug Delivery Systems; Additive Manufacturing; Controlled; Drug Release; Intelligent Drug Delivery Systems; Multi-Drug Delivery; Pharmaceutical 4D Printing; Polypills; Personalised Medicine; Precision Therapeutics; Responsive Hydrogels; Shape-Memory; Polymers; Smart Biomaterials; Stimuli-Responsive Polymers